Water vapor sorption kinetics of polymer based sorbents: Theory and experiments. (5th August 2016) - Sultan, Muhammad; El-Sharkawy, Ibrahim I.; Miyazaki, Takahiko; Saha, Bidyut B.; Koyama, Shigeru; Maruyama, Tomohiro; Maeda, Shinnosuke; Nakamura, Takashi
Graphical abstract: Arrhenius plot of two novel polymer based sorbents, PS-I/water and PS-II/water pairs. Highlights: Linear driving force model of sorption kinetics is modified for studied pairs. Modified model is successfully validated for short-time and long-time estimations. Activation energy and pre-exponential constant are obtained from Arrhenius plots. Influence of P/Po and Tads on diffusion time constant is investigated. Abstract: Water vapor sorption kinetics of two polymer based sorbents has been experimentally measured at adsorption temperatures of 20, 30, 50, 70 and 80 °C using a magnetic suspension adsorption measurement unit. The experimental data is employed to commonly known adsorption kinetics approximations i.e. Linear driving force (LDF) model, Fickian diffusion (FD) model, and Semi-infinite model. All these models could not approximate the adsorption kinetics of polymer based sorbents, however, the LDF model is modified which successfully predicts the experimental kinetics for short-time and long-time estimation. For both sorbents, the diffusion time constant has been calculated at each adsorption temperature, and consequently, activation energy and pre-exponential constant are found from Arrhenius plot. The variation of diffusion time constant with relative pressure and adsorption temperature is discussed in relation with typical behavior of polymer/water pairs.